Students' Perception on the Use of Pop Songs in English Language Learning - Dorkas Aditya Anjana; Listyani Listyani; Audi Yundayani (Prominent, 2026)
English is an international language, which in the globalization era is a mandatory to master and taught in schools. However, sometimes it is still encountered where the process of learning English at school is scary and boring for students. This research aims to describe the use of pop songs in English language teaching, using descriptive qualitative and involved describing and providing important information from the research. Interview, observation, and documentation were used in collecting data. This research found that English songs could help students in their learning process, especially improving their learning motivation and desire to learn English. Students enjoyed learning songs because it made them not feel bored. Moreover, students could learn new vocabulary and pronunciation from the songs. However, there were also some challenges that were faced by the students because not all students could have good concentration in learning English while listening to pop songs. The English pop song can be incorporated into the English language teaching process to encourage students to engage with authentic materials and embrace the English learning process without fear by considering students' needs and characteristics and concentrating on achieving the learning objective.